Survey in Hydrazine and its Preparation, Reactions, and Their Applications - Safa Saleem Zayed; Noor Sabah Muttaleb; Noor Saad Jafar; Nagham Mahmood Aljamali (International Journal of Photochemistry and Photochemical Research, 2026)
This review concerned with hydrazine derivatives; Hydrazine is an important chemical compound used in jet engine and rocket fuel. Therefore, the European Union prohibits its sales to the developing world at 100% concentration and only permits its sales at 20-25% concentration. It is also used in industry to produce chemicals for textiles, agriculture, photographic development materials, and blowing agents used in the manufacture of foam rubber. It is also used to absorb dissolved oxygen in water to prevent corrosion in high-pressure and high-temperature steam boilers, such as in power plants. Hydrazine derivatives are used to regulate plant and weed growth. Its salt (hydrazine sulfate, [N2H5] HSO4) is also used as a promising treatment for some cancers and for treating weakness and emaciation. Its compound, hydrazine peroxide, is considered one of the most powerful and rapid explosives. Hydrazine has a strong smell and is a colorless liquid. It is an effective reducing agent. This substance has the chemical formula NH2NH2, boils at 114°C, and blends readily with alcohol and water. It ignites easily in air, producing a lot of heat that forms water and nitrogen gas. Drug Synthesis: The pharmaceutical industry uses hydrazine hydrate to make medications for diabetes and some forms of tuberculosis. Hydrazine hydrate is frequently utilized as a major raw material in drug production because of its potent lowering capabilities. For instance, hydrazine hydrate is essential to the synthesis of anti-tuberculosis medications like benzyl sulfonyl hydrazide and isoniazid. They are essential to the synthesis of dyes, especially triphenylmethane and azo dyes. Because of their excellent durability and vivid hues, these dyes are commonly employed in sectors including leather and textiles. Another essential ingredient in the creation of some organic color goods is hydrazine hydrate.
Keywords: Chalcone; Hydrazine; compound; cycle; heterocycle; hydrazone